A Play: Cries from Gaza, Mirrors of Resilience and the Geography of Struggle - Dr. Nawel Meddouri; Dr. Nassira China (ROSSIISKAYA ISTORIYA, 2026)
This study examines how the Palestinian issue is manifested in Iraqi theatre following the events of 7 October 2023, using a dramatic reading of Cries from Gaza by Mohamed Sakhi al-Itabi as a case study. The study is based on the idea that theatre is a form of art that can express human concerns and their various social, political and cultural aspects. Historically, Palestinian theatre has been linked to defending national identity and representing the suffering and struggle of the Palestinian people to regain their historic and geographic rights. Developments in the Palestinian cause, particularly the war on Gaza, have contributed to reshaping Arab theatrical discourse. Playwrights have turned to documenting the crimes committed by the Zionist occupation, exposing the falsity of its media narrative and highlighting the steadfastness of the Palestinian people in the face of policies of annihilation and displacement. In this context, Iraqi theatre has emerged as a creative space that aligns with Palestinian resistance. It draws upon symbols, historical events and religious discourse to entrench the centrality of Jerusalem and Gaza in Arab consciousness. Cries from Gaza reveals the presence of a revolutionary and resistant dimension within contemporary Iraqi theatrical discourse. This is achieved by portraying the suffering of Palestinians and documenting their heroism and resilience, reflecting theatre's engagement with current events and its transformation into a tool of cultural resistance against attempts at erasure and forced displacement. Accordingly, the dramatic text functions as an artistic and historical document that contributes to preserving Palestinian memory and strengthening awareness of the cause at Arab and human levels.